Beyond Aesthetics: Players, Player-Characters and Interactivity-as-Demand in Cozy Games - Boudreau, Kelly (Replay. The Polish Journal of Game Studies, 2024)
Cozy games are often defined by their soft visual design, ambient audio, and low risk gameplay that addresses a range of themes from casual to meaningful. Typically, they also center on simple gameplay in terms of control schema and the ability to disconnect, as a safe, relaxing play space, and with its easy exits points to quit the game. While these aspects have been discussed in both scholarly and media entertainment writing, the demands (or lack thereof) have yet to be explored from a theoretical perspective. Through the lens of interactivity-as-demand theory, this paper aims to explore the connection between the gameplay experience as it relates to cognitive, physical, social, and emotional demands and the in-game representations of the player-character. Through this analytical lens, it is possible to understand the consistency and disconnect of demands as experienced by the player compared to how they are (re)presented on screen which has potential implications related to the player’s expectations and design principles of cozy games.